2014
DOI: 10.1111/head.12317
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Brain Tumor Headache

Abstract: There is an increasing overlap between the primary and secondary headaches and they may actually share a similar biological mechanism. While there can be some criticism that the experimental work with dural and arterial stimulation produced head pain and not actual headache, when considered with the clinical observations about headache type, coupled with improvement after treatment of the primary tumor, we believe that traction on these structures, coupled with increased intracranial pressure, is clearly part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…29 A number of studies evaluating pain after microsurgery have demonstrated that retrosigmoid craniotomy has a higher early prevalence of headache compared with translabyrinthine and middle fossa resection. 19,28,36,37,45 There are many explanations for this finding. Several studies have demonstrated a reduction in postoperative headache after using cranioplasty, suggesting that adhesions between nuchal muscles and posterior fossa dura may cause pain.…”
Section: Impact Of Treatment On Headachementioning
confidence: 97%
See 2 more Smart Citations
“…29 A number of studies evaluating pain after microsurgery have demonstrated that retrosigmoid craniotomy has a higher early prevalence of headache compared with translabyrinthine and middle fossa resection. 19,28,36,37,45 There are many explanations for this finding. Several studies have demonstrated a reduction in postoperative headache after using cranioplasty, suggesting that adhesions between nuchal muscles and posterior fossa dura may cause pain.…”
Section: Impact Of Treatment On Headachementioning
confidence: 97%
“…Although there are currently no studies in the VS literature focusing on longitudinal change in headache symptoms following SRS and conservative observation, surgical series have reported a frequency of baseline headache ranging from 9% to 50% and a prevalence of posttreatment headache ranging from 0% to 75%. 17,24,28,37,38,44,45,47 The low rate of headache seen in some studies is perplexing since, within the general population, the estimated lifetime prevalence of headache is approximately 60%-80%, with roughly 40%-60% of individuals experiencing headaches each year. 42,43 This significant disparity probably stems from heterogeneous study methodology, varying definitions of headache, and differing lengths of follow-up.…”
Section: Prevalence Of Headache In Patients With Sporadic Vsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Nelson and Taylor revisit headaches associated with intracranial tumors, a topic that always attracts practitioners' interest . The reasons for this attention are obvious; no practitioner wants to overlook any (potentially) treatable cause of a patient's head pain.…”
Section: 4 Headache Attributed To Intracranial Neoplasiamentioning
confidence: 99%
“…In addition, it is estimated symptomatic in 40% of cases. When present, symptoms include headaches, epilepsy due to cerebral hemorrhage and other symptoms depending on the site of the lesion 25. Therapeutical options available for patients who have found to have a cavernous malformation are surgery and “stand and wait” approach, depending upon the gravity of each case 6.…”
Section: Introductionmentioning
confidence: 99%